Calculated conjugated payload from immunoassay and LC–MS intact protein analysis measurements of antibody-drug conjugate. (November 2016) - Rago, Brian; Clark, Tracey; King, Lindsay; Zhang, Jenny; Tumey, L Nathan; Li, Fengping; Barletta, Frank; Wei, Cong; Leal, Mauricio; Hansel, Steve; Han, Xiaogang
Aim: Complex nature of bioconjugates require multiple bioanalytical approaches to support PK and absorption, distribution, metabolism and excretion characterization. For antibody-drug conjugate (ADC) bioanalysis both LC–MS and ligand-binding assays (LBAs) are employed.Results: A method consisting of immunocapture extraction of ADC from biomatrices followed by LC–MS analysis of light and heavy chain is described. Drug antibody ratio (DAR) profiles of ADC Tras-mcVC-PF06380101 dosed at 0.3, 1 and 3 mg/kg in Sprague Dawley rats were obtained. Combined with total antibody (monoclonal antibody) measurement by LBA, conjugated payload concentration was calculated.Conclusion: PK profiles from LBA, ADC and calculated conjugated payload (DAR × monoclonal antibody) were in good agreement. We present a new tool for PK assessment of ADCs while also exploring ADC metabolism and DAR sensitivity of LBA ADC assay.